ПРОСВІТНИЦЬКО-КУЛЬТУРНИЙ ВПЛИВ ІСТОРИЧНИХ ТРАНСФОРМАЦІЙ СУСПІЛЬСТВА НА ФОРМУВАННЯ ОСОБИСТОСТІ Я. Ф. ЧЕПІГИ - Bogdanets-Biloskalenko, N (Continuing Professional Education: Theory and Practice, 2019)
In the article opens up forming of personality of scientist-teacher Ya.Chepigi under act of historical transformations of society. Appeal attention on research of scientist in industry of pedagogics and pedology. In particular Jacob Chepiga wrote scientifi c labours with the purpose of improvement of society in these industries. Special value there is labour of «Self-education of teacher in this direction». Leaning against experience of formation of other states, with lightness designed the new ideas of the West on national Ukrainian subsoil. It is such ideas, as само- розвиток of personality, labour method and others like that. Categorically and sharply enough вислослювався against denationalization of school and on defence of national idea, етнопси- хологічні defended principles in education of child. His activity has creation of national school a main accent